THE CONTRIBUTION OF WORK ENVIRONMENT, DISCIPLINE, AND COMPENSATION TO THE PRODUCTIVITY OF EMPLOYEES WORKING FROM HOME (WFH) - Sumarno (Universitas Sarjanawiyata Tamansiswa, 2025)
The COVID 19 pandemic has significantly altered work patterns across various sectors, including the widespread adoption of Work from Home (WFH) systems. This study aims to analyze the influence of work environment, work discipline, and compensation on employee performance during remote work. A quantitative approach was employed using a survey method. The sample consisted of 110 employees of CV. Cahaya Mandiri selected through simple random sampling. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression. The results revealed that the three independent variables work environment, work discipline, and compensationhave both simultaneous and partial significant effects on employee performance. The coefficient of determination (R²) was 0.216, indicating that 21.6% of the variation in employee performance can be explained by these three variables. These findings underscore the importance of fostering a supportive work environment, enhancing employee discipline, and providing fair compensation to improve employee productivity in remote work settings.